The Mexican Women during the government of Lázaro Cárdenas, 1934-1940 - Montes de Oca Navas, Elvia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper addresses the issue of women in the early twentieth century, especially during the government of Lázaro Cárdenas (1934-1940). The central hypothesis of this paper is that even if the government policies and in some print media, such as the newspapers and textbooks at the Cardenas government time, proposed social conditions in relation how women lived and their relationships with men, these conditions did not change in a structural way, and they were reinforced by the social imaginary. The main objective of the document was to determine the hypothesis presented above and as a methodology there was the analysis of some primary sources of information, such as newspapers and textbooks, and in the conclusion it is reinforced the hypothesis planned.